Forensic identification of four Indian snake species using single multiplex polymerase chain reaction - Ishani Mitra; Soma Roy; Ikramul Haque (Wolters Kluwer Medknow Publications, 2022)
Among different endangered animal species, snakes are the most neglected creature looked at with apathy and therefore, are ruthlessly killed, illegally trafficked, and poached for their venom, lucrative skin, meat, and bones for manufacturing of medicines, accessories, and food items. Establishing the identity of the endangered snake species is important for punishing the offenders under Wildlife Protection Act (WPA) (1972) but morphological characters fail to establish identity as they are often altered. The technique of identification of snake species at molecular level holds very effective conclusion in punishing offender. Here, we have constructed and demonstrated a novel multiplexing polymerase chain reaction technique, using 16S rRNA and C-mos gene for identification of four Indian snake species, namely Ptyas mucosa, Daboia russellii, Naja naja, and Xenochrophis piscator. They are listed in Appendix-II and III of convention on international trade in endangered species of wild fauna and flora and Schedule II; Part II of Indian WPA, 1972. Therefore, it may be considered a functional tool for establishing species-specific identity of four Indian snake species and promising to be useful for their conservation.